2008
DOI: 10.1002/ajim.20644
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors and shoulder symptom development among workers

Abstract: Using self-reporting to determine demand-control quadrants was successful in identifying subjects at risk of developing work-related shoulder symptoms. Research is needed to determine if this relationship holds with clinically diagnosed shoulder and other upper extremity musculoskeletal disorders. This may be part of a simple tool for assessing risk of developing these UEMSDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Three reviews reported that both repetitive and overhead work are risk factors for musculoskeletal disorders of the shoulder (5,44,45). One recent review found that shoulder symptoms occurred more frequently in subjects working in passive jobs (low demand andcontrol) or high-strain jobs (high demand, low control) (46). Furthermore, particular combinations of exposures (eg, holding a tool while working overhead) were associated with increased prevalence of musculoskeletal disorders at the shoulder (44).…”
Section: Discussionmentioning
confidence: 99%
“…Three reviews reported that both repetitive and overhead work are risk factors for musculoskeletal disorders of the shoulder (5,44,45). One recent review found that shoulder symptoms occurred more frequently in subjects working in passive jobs (low demand andcontrol) or high-strain jobs (high demand, low control) (46). Furthermore, particular combinations of exposures (eg, holding a tool while working overhead) were associated with increased prevalence of musculoskeletal disorders at the shoulder (44).…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al (15) found that having either a passive or high-strain job was associated with higher incidence of shoulder symptoms. The same was true for low control.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying principle is that workrelated stress, measured by levels of job demands and control (demand-control quadrants), can affect workers' health. Several studies have investigated how this interaction between job demands and job control is related to MSD development in industrial workers (15)(16)(17), but only a few have looked into the prevalence of MSDs among healthcare workers. This issue is particularly poorly covered in the nursing profession.…”
mentioning
confidence: 99%
“…Seven of the studies specifically examined life events, finding statistically significant associations with work injury, although these life events were not generally related to family health. More recent research on the relationship between work stress and work injury has generally found that higher work stress, or some components of work stress (high demand, low control, low support), have a statistically significant association with higher injury rates [Low et al, 1996;Murata et al, 2000;Li et al, 2001;Nolting et al, 2002;Wilkins and MacKenzie, 2007;Salminen et al, 2003;Swaen et al, 2004;Nakata et al, 2006;Soori et al, 2008;Smith et al, 2009].…”
mentioning
confidence: 96%